2007
DOI: 10.1093/heapol/czm015
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to hospital care for the poor: comparative analysis of four health equity funds in Cambodia

Abstract: There is a large body of evidence that user fees in the health sector create exclusion. Health equity funds attempt to improve access to health care services for the poorest by paying the provider on their behalf. This paper reviews four hospital-based health equity funds in Cambodia and draws lessons for future operations. It investigates the practical questions of 'who should do what and how'. It presents, in a comparative framework, similarities and differences in objectives, the actors involved, design asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 36 publications
3
68
0
Order By: Relevance
“…The second phase of our study showed that, depending on the type and location of the facility, up to 28% of HEF-funded patients now using health facilities did not attend public facilities before having an HEF card and that the majority cited financial constraints as the reason. Using a different methodology, this confirms findings by Noirhomme et al 10 and other studies. 6,9,12 These data confirm that the financing role of HEFs addresses the unmet health-care needs of poor families.…”
Section: Addressing Access Barrierssupporting
confidence: 92%
See 2 more Smart Citations
“…The second phase of our study showed that, depending on the type and location of the facility, up to 28% of HEF-funded patients now using health facilities did not attend public facilities before having an HEF card and that the majority cited financial constraints as the reason. Using a different methodology, this confirms findings by Noirhomme et al 10 and other studies. 6,9,12 These data confirm that the financing role of HEFs addresses the unmet health-care needs of poor families.…”
Section: Addressing Access Barrierssupporting
confidence: 92%
“…Our study confirmed that HEF patients did not face stigma, were rarely charged unofficial fees (thanks to procedures put in place by HEF schemes) and that HEFs helped to improve overall quality of care. Noirhomme et al 10 confirmed that contracting arrangements adopted by HEF schemes ensure accountability of health-care providers and set quality standards.…”
Section: Addressing Access Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In addition, at the end of 2007, the government introduced the nationwide Midwife Incentive Scheme, which pays midwives 10 United States dollars (US$) for each live birth they attended in a referral hospital and US$ 15 for each delivery they attended in a health centre, on top of the fee charged to the patient.…”
mentioning
confidence: 99%
“…Other studies also found that identification of HEF fund recipients would have been more successful and effective if done by community members. Such community involvement was found to be feasible and accrues minimal direct costs (Jacobs & Price, 2006;Noirhomme et al, 2007). Specifically, pagoda-managed equity funds resulted to higher community participation, while indigenous community-based organisations resulted to reduced administrative costs (Noirhomme et al, 2007).…”
Section: Estimation Results For Infant Mortality Rates Total Fertilimentioning
confidence: 98%